Two Roles for the Leucine-Responsive Regulatory Protein in Expression of the Alanine Catabolic Operon (dadAB) in Klebsiella aerogenes - Janes, Brian K. (American Society for Microbiology, 1999)
The lrp gene, which codes for the leucine-responsive regulatory protein (Lrp), was cloned from Klebsiella aerogenes W70. The DNA sequence was determined, and the clone was used to create a disruption of the lrp gene. The lack of functional Lrp led to an increased expression of the alanine catabolic operon (dad) in the absence of the inducer l-alanine but also to a decreased expression of the operon in the presence of l-alanine. Thus, Lrp is both a repressor and activator of dad expression. Lrp is also necessary for glutamate synthase formation but not for the formation of two other enzymes controlled by the nitrogen regulatory (Ntr) system, glutamate dehydrogenase and histidase.